Investigating The Relationship Linking Self Management Of Learning And M-Learning (SAAS Model) Adoption In Higher Learning Institutions: A Case Of Africa Nazarene University, Nairobi. (International Journal of Engineering and Computer Science, 2017)
The objective of the paper was to determine the relationship linking self-management of learning and students’ behavioral intention to adopt and use M-learning (SaaS model) in Africa Nazarene University. The Extended Unified Theory of Acceptance and Use of Technology (UTAUT) model was used as the foundation theory of this paper, and the data was collected using questionnaires. The questionnaires were analyzed for correlation, significance and variance, to study M-learning (SaaS model) adoption and use based on self-management of learning. The results of the paper revealed that there is no positive relationship between self-management of learning with students’ behavioral intention to adopt and use M-learning in Africa Nazarene University. The study recommends that, universities should integrate mobile learning (SaaS model) into their strategic plan in order to improve mobility in the learning activity as well as school and institutional wide strategies for mobile learning.